(3GdeOhfI aj Gdabg GdeGdcis - (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s; (3QhGjI SMfhf Hf SYjO GdJfhMis ((3YHO Gdedc Hf eSQI GdjMUHi s)
(3ChdgG (B:s
(3ai GdfPQ ai eYUjI Ch WGYI s
(3BNQgG (B:s
(3bdJ (B: (3hjJHY GdZdGe hEf eVi GdCLd hgh YfOg de jYJb ai bhd eGdc ? bGd (B:(3fYe Je cJGH GdfPRQ GdKGfi HMeO Gddg hYhfg s
(3bWYI efgG JTJed Ydi cJGH GdfPhQ GdKGfis
(3fSNI Ydi Qb ZRGds
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1644s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs